Fresh osteochondral allograft transplantation (FOCAT) for definitive management of a 198 square millimeter osteochondral lesion of the talus (OLT): A case report. (March 2021) - Merritt, Gerald; Epstein, Josh; Roland, Derrick; Bell, Daniel
Highlights: An osteochondral lesion of the talus (OLT) is an idiopathic acquiredlesion of the subchondral bone that can lead to debilitating sequelae. The causes of OLT's are still debatable, however, most agree that the etiology is repetitive microtrauma associated with vascular impairment. OLTs are most commonly described in the medial portion of the talus, while lateral involvement is less frequent. If not properly recognized and treated, an OLT may lead to numerous secondary conditions including premature osteoarthritis and functional limitations of the ankle joint. Multiple surgical and non-surgical treatment modalities have been described with varying results. Treatments are usually guided by the patients age, onset of symptoms, severity, and the disease stage according to the Berndt and Harty classification. Recent literature recommends curettage, drilling, or microfracture techniques for lesions which are no larger than 15 mm in diameter and no deeper than 7 mm. On the other hand, for large lesions or lesions that failed from primary bone marrow stimulation, surgery should be considered for autologous chondrocyte implantation (ACI), osteochondral autograft transplantation (OATs or mosaicplasty), or osteochondral allograft transplantation [1 ]. This case study examines surgical treatment of an extensive OLT in a 53 year old man who suffered with continuous ankle pain for over 10 years, misdiagnosed as ankle joint arthritis. Abstract: An osteochondral lesion of the talus (OLT) is an idiopathic acquired lesion of the subchondral bone that can lead to debilitating sequelae. The causes of OLT's are still debatable, however, most agree that the etiology is repetitive microtrauma associated with vascular impairment. OLTs are most commonly described in the medial portion of the talus, while lateral involvement is less frequent. If not properly recognized and treated, an OLT may lead to numerous secondary conditions including premature osteoarthritis and functional limitations of the ankle joint. Multiple surgical and non-surgical treatment modalities have been described with varying results. Treatments are usually guided by the patients age, onset of symptoms, severity, and the disease stage according to the Berndt and Harty classification. Recent literature recommends curettage, drilling, or microfracture techniques for lesions which are no larger than 15 mm in diameter and no deeper than 7 mm. On the other hand, for large lesions or lesions that failed from primary bone marrow stimulation, surgery should be considered for autologous chondrocyte implantation (ACI), osteochondral autograft transplantation (OATs or mosaicplasty), or osteochondral allograft transplantation [1 ]. This case study examines surgical treatment of an extensive OLT in a 53 year old man who suffered with continuous ankle pain for over 10 years, misdiagnosed as ankle joint arthritis. Level of clinical evidence: Level of evidence 4.